STRATEGI VIRAL MARKETING PT FLIP MENGGUNAKAN E-WOM DALAM PEMBENTUKAN BRAND AWARENESS (WWW.FLIP.ID) - Arini Kusumawardhani; Dini Salmiyah Fithrah Ali (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
Viral marketing using electronic word of mouth (e-WOM) is one of the important activities implemented by a company in the process of creating brand awareness. One of the strategies is a website. A website becomes the tools that use by the consumers and have one-to-many relationship. A website is also a credibility and an image to a company, through contents that presented on the website can influence the characteristic of electronic word of mouth (e-WOM) messages. The strategy is usually done by start-up companies like PT Flip, which aims to introduce the free inter-bank transfer service through their site www.flip.id. This study aims to determine how the viral marketing of PT Flip using electronic word of mouth (eWOM) in creating brand awareness through website. This study uses a descriptive qualitative methodology approach and supported by constructivism paradigm. The data in this study was obtained through direct and deep interviews with three persons of PT Flip as key informant and a viral marketing expert as supported informant, also literature, audio and visual documentation. The results of this study is viral marketing strategies that implemented by PT Flip using electronic word of mouth (e-WOM) through website, using elements of the website such as context, content, customization, communication, and connection to bring interactivity and electronic word of mouth (e-WOM). From the application of these elements are formed brand awareness at the level of brand recognition.